The Role of Indigenous Storytelling in Shaping Cultural Values through Visual Book Design - Siti Ansoriyah; Reni Oktaviani; Nadhifa Indana Zulfa Rahma (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2025)
This study explores the role of traditional storytelling in shaping cultural values through visual book design as a contextual educational medium. A descriptive qualitative approach was employed, collecting data through in-depth interviews, participatory observations, and documentation of eight key informants, educators, artists, and indigenous leaders, selected until data saturation was reached. Data were analyzed thematically using NVivo, with examples of codes, categories, and excerpts provided to enhance transparency. The study was conducted in several regions, making the findings exploratory rather than generalizable to the whole of Indonesia. Visualization of traditional stories in picture books effectively instilled values such as mutual cooperation, respect for ancestors, and ecological wisdom in elementary school children. Story visualization also strengthened moral understanding and students’ emotional engagement in the learning process. Integrating traditional stories into visual book design supports the preservation of local culture and serves as a relevant pedagogical strategy in value education based on local wisdom.